2010
DOI: 10.1242/dev.042036
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila nuclear receptors DHR3 and βFTZ-F1 control overlapping developmental responses in late embryos

Abstract: SUMMARYStudies of the onset of metamorphosis have identified an ecdysone-triggered transcriptional cascade that consists of the sequential expression of the transcription-factor-encoding genes DHR3, FTZ-F1, E74A and E75A. Although the regulatory interactions between these genes have been well characterized by genetic and molecular studies over the past 20 years, their developmental functions have remained more poorly understood. In addition, a transcriptional sequence similar to that observed in prepupae is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 51 publications
(72 reference statements)
1
72
0
Order By: Relevance
“…Previous studies demonstrated that ftz-f1 dictates the temporal specificity of ecdysone signaling by integrating messages between numerous nuclear receptors (E75, DHR3, DHR4, and potentially also E78 and DHR39) (36,37). Despite its long-known expression in the nervous system, the only reported role for ftz-f1 in nervous system metamorphosis, to our knowledge, is in the remodeling of mushroom body neuron morphology (47)(48)(49)(50). Here, we describe a role for ftz-f1 in triggering timed neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that ftz-f1 dictates the temporal specificity of ecdysone signaling by integrating messages between numerous nuclear receptors (E75, DHR3, DHR4, and potentially also E78 and DHR39) (36,37). Despite its long-known expression in the nervous system, the only reported role for ftz-f1 in nervous system metamorphosis, to our knowledge, is in the remodeling of mushroom body neuron morphology (47)(48)(49)(50). Here, we describe a role for ftz-f1 in triggering timed neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mutations in the genes coding for the enzymes that convert cholesterol into 20-hydroxyecdysone, the active form of ecdysone, cause developmental arrest at mid-embryogenesis and formation of a very reduced cuticle (Chavez et al, 2000;Ono et al, 2006;Petryk et al, 2003). The phenotypes of ecdysone-deficient embryos are strong compared to those resulting from defects in ecdysone transduction mediated for example by E75 or b-FtzF1 (Reinking et al, 2005;Ruaud et al, 2010) arguing that multiple transcription factors cooperate to transduce the ecdysone signal during cuticle differentiation. It will be a great and fruitful challenge to dissect these pathways downstream of ecdysone in the D. melanogaster embryo.…”
Section: Ecdysone Drives Multiple Pathways Of Cuticle Differentiationmentioning
confidence: 99%
“…We have directly shown that DHR3, via the interaction with SAYP, drives the expression of several SAYP-dependent genes in cell culture. The above genes have not been recognized as components of the ecdysone cascade, 15 which is evidence that the effect of ecdysone stimulation may be much wider than expected previously. transcription before and after DHR3 induction with ecdysone (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 83%
“…DHR3 is essential in embryogenesis, during larval development and in the initiation of metamorphosis. [15][16][17] Although the biological function of DHR3 in Drosophila development has been well characterized, the molecular mechanism of its action has remained obscure.…”
Section: Introductionmentioning
confidence: 99%